Binary Surfactant–Mediated Tunable Nanotip Growth on Gold Nanoparticles and Applications in Photothermal Catalysis - Mi, Xiaohu; Zhang, Tingting; Zhang, Baobao; Ji, Min; Kang, Bowen; Kang, Chao; Fu, Zhengkun; Zhang, Zhenglong; Zheng, Hairong (Frontiers in Chemistry, 2021)
Plasmonic nanostructures with sharp tips are widely used for optical signal enhancement because of their strong light-confining abilities. These structures have a wide range of potential applications, for example, in sensing, bioimaging, and surface-enhanced Raman scattering. Au nanoparticles, which are important plasmonic materials with high photothermal conversion efficiencies in the visible to near-infrared region, have contributed greatly to the development of photothermal catalysis. However, the existing methods for synthesizing nanostructures with tips need the assistance of poly(vinylpyrrolidone), thiols, or biomolecules. This greatly hinders signal detection because of stubborn residues. Here, we propose an efficient binary surfactant–mediated method for controlling nanotip growth on Au nanoparticle surfaces. This avoids the effects of surfactants and can be used with other Au nanostructures. The Au architecture tip growth process can be controlled well by adjusting the ratio of hexadecyltrimethylammonium bromide to hexadecyltrimethylammonium chloride. This is due to the different levels of attraction between Br−/Cl− and Au3+ ions. The surface-enhanced Raman scattering and catalytic abilities of the synthesized nanoparticles with tips were evaluated by electromagnetic simulation and photothermal catalysis experiments (with 4-nitrothiophenol). The results show good potential for use in surface-enhanced Raman scattering applications. This method provides a new strategy for designing plasmonic photothermal nanostructures for chemical and biological applications.